Single-cell analysis reveals tumour size as a key driver of immune cell profile alterations in primary breast tumours and corresponding lymph nodes - Marit Otterlei Fjørtoft; Øystein Garred; Ole Christian Lingjærde; Karin Teien Lande; Lars Ottestad; Inger Riise Bergheim; OSBREAC; Jon Lømo; Colin LaMont; June Helen Myklebust; Hege Russnes; Kanutte Huse; et al. (BJC Reports)
Abstract Background At diagnosis, 30–40% of women with breast cancer have metastases in sentinel (SN) or axillary lymph nodes (ALN). Nodal status is a strong prognostic factor and guides treatment decisions. Immune checkpoint inhibition has shown some efficacy, which can increase in the neoadjuvant setting. A better understanding of how tumour cells in primary tumours and metastatic lymph nodes shape the local immune microenvironment may provide clues for more individualized therapeutic interventions. Methods We conducted deep immunophenotypic analysis of 29 primary breast tumours and 36 lymph nodes from 38 patients with primary operable breast cancer. Results The immune profile of the primary tumour was not predictive of the lymph node immune profile or metastatic status. Primary tumours showed prominent CD8 T cell exhaustion and activated regulatory T cells, and the frequencies of these subsets were associated with tumour size. The immune cell profile in lymph nodes were different from the profile in primary tumours, except for the ALN+ nodes, which displayed a T-cell profile more similar to primary tumours. The frequencies of the T cell subsets in lymph nodeswere associated with metastatic size. Tumour cells from smaller metastases exhibited a distinct phenotype compared to those from larger tumour deposits, and the size of the tumour cell deposit impacted the local immune cell composition. Conclusion The tumour size of primary tumours and metastatic size in lymph nodes are the main drivers of changes in immune cell composition.